2018
DOI: 10.1007/s00107-018-1305-0
|View full text |Cite
|
Sign up to set email alerts
|

Bondline shear strength and wood failure of European and tropical hardwood glulams

Abstract: The study reports on block shear investigations with bondlines of face-glued laminations and matched solid wood specimens from hardwood glulam (GLT) beams produced industrially from eight technically and stand volume-wise important species. The European hardwoods comprised oak, beech, sweet chestnut and ash and the tropical species were teak, keruing, melangangai and light red meranti. The adhesives were phenol-resorcinol and melamine-urea. When combining all species in one sample, a rather strong linear relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 21 publications
1
24
1
1
Order By: Relevance
“…provide the best available basis for comparison. In that way, findings of the current study are not consistent with those of Aicher et al (2018). In block shear tests conducted on specimens originating from industrially manufactured hardwood glued-laminated timber beams, common ash attained higher wood and bondline shear strengths than common/sessile oak with density of 695 kg/m 3 and 752 kg/m 3 , respectively.…”
Section: Comparison Of Results With Requirements From Glt Standards Acontrasting
confidence: 99%
See 2 more Smart Citations
“…provide the best available basis for comparison. In that way, findings of the current study are not consistent with those of Aicher et al (2018). In block shear tests conducted on specimens originating from industrially manufactured hardwood glued-laminated timber beams, common ash attained higher wood and bondline shear strengths than common/sessile oak with density of 695 kg/m 3 and 752 kg/m 3 , respectively.…”
Section: Comparison Of Results With Requirements From Glt Standards Acontrasting
confidence: 99%
“…However, the significance of this criterion should be interpreted with caution because values from this standard do not account for variation within species. As suggested by River et al (1991) and Aicher (2018), comparing the bondline shear strength with a clear wood strength value obtained from the same sample of wood material would be more meaningful. Moreover, the shear strength should always be interpreted in conjunction with the level of wood failure.…”
Section: Comparison Of Results With Requirements From Glt Standards Amentioning
confidence: 96%
See 1 more Smart Citation
“…However, despite its superior mechanical performance, hardwood is still less used in timber structural applications (Schlotzhauer et al 2019). For example, surveys (Aicher et al 2018;Kobel et al 2014) showed that most of the glulam products are made of softwood worldwide. One of the contributing factors is the large quality variations existed in hardwood logs and the significant cost associated with processing the logs.…”
Section: Introductionmentioning
confidence: 99%
“…La redacción de la norma para especies de frondosas se encuentra en el Comité Europeo de Normalización a la espera de información consistente que permita establecer los requisitos de fabricación correspondientes. La generación de datos experimentales relacionados con el comportamiento de la línea de cola y la resistencia de corte para MLE fabricada a partir de la extensa variedad y heterogeneidad de especies de frondosas es una ardua tarea, que ha llevado a países no europeos como Estados Unidos y Japón, a formar grupos de especies y rangos de densidad, para definir los requisitos de fabricación para MLE de frondosas (Aicher et al 2018). Independientemente de las especies, todas estas normas establecen una serie de parámetros de fabricación dentro de los cuales se incluyen: las características del adhesivo, el diente para la fabricación del endentado de las láminas, la presión aplicada, el contenido de humedad de la madera, y las condiciones climáticas (temperatura y humedad relativa) del recinto de producción.…”
Section: Introductionunclassified